Anti-Müllerian hormone levels and fecundability in women with a natural conception. (October 2017) - Hvidman, Helene W.; Bang, Anne Kirstine; Priskorn, Lærke; Scheike, Thomas; Birch Petersen, Kathrine; Nordkap, Loa; Loft, Anne; Pinborg, Anja; Tabor, Ann; Jørgensen, Niels; Nyboe Andersen, Anders
Abstract: Objectives: To investigate the association between anti-Müllerian hormone (AMH), a well-established marker of the ovarian reserve, and time-to-pregnancy (TTP) in natural conceptions, and to assess changes in serum-AMH in early pregnancy. Study design: A cross sectional study comprising 279 women aged 21–42 years with a natural conception recruited during 2012–2014. AMH was measured in gestational week 10–19. AMH z-scores (z-AMH) adjusted for gestational week at blood sampling were categorised in the 1st, 2nd–4th (reference), and 5th quintile. Data were analysed by discrete-time survival-analysis and results presented as odds ratios (OR), 95% confidence interval (CI); OR <1 indicating a longer TTP and OR >1 indicating a shorter TTP. Results: The median AMH-level was 23.0 (range: <3.0;144.0) pmol/l, and serum-AMH decreased by 7.5% (95% CI:-12.0%;-2.8%) per gestational week. Mean ± SD female age was 30.9 ± 3.6 years. The median TTP was 2 (range: 1–32) months. After adjustment for possible confounders including total sperm count, TTP was unrelated to female age (aOR:1.0, 95% CI:0.9;1.0) and continuous z-AMH (aOR:0.8, 95% CI:0.7;1.0), but women in the low z-AMH group had a shorter TTP than the reference group (aOR:1.7, 95% CI:1.1;2.7). TTP was prolonged in preconception oral contraceptive (OC) users (aOR:0.7, 95% CI:0.5;1.0, p = 0.04). Compared with women having used OC <2 years, TTP was significantly longer in women having used OC for 2–12 years (aOR:0.5, 95% CI:0.2;1.0, p = 0.048) and >12 years (aOR:0.4, 95% CI:0.2;0.9, p = 0.022) after age-adjustment. Conclusions: TTP was unrelated with z-AMH when modelled as a continuous covariate. Unexpectedly, TTP was shorter in the low z-AMH group. Natural conception was observed in women with a wide range of AMH-levels including women with undetectable serum-AMH. A continuous decrease in serum-AMH was observed during first and second trimester. Preconception OC-use was identified as an independent predictor of a prolonged TTP, and the duration of OC-use appeared to influence the delay in conception. Although this is presently one of the largest studies investigating the association between AMH and fecundability in fertile women, the study has some limitation including a relatively low participation rate and a risk of selection bias in addition to AMH assessment in pregnancy and a retrospective collection of TTP and OC-use associated with a risk of recall bias. These limitations may explain the unexpected finding of a shorter TTP in the low z-AMH group.